Effect of central JAZF1 on glucose production is regulated by the PI3K‐Akt‐AMPK pathway. Issue 5 (10th April 2020) - Zhou, Mengjiao; Xu, Xiaohui; Wang, Han; Yang, Gangyi; Yang, Mengliu; Zhao, Xinyi; Guo, Huilin; Song, Jinlin; Zheng, Hongting; Zhu, Zhiming; Li, Ling
Abstract: The role of central juxtaposed with another zinc finger gene 1 (JAZF1) in glucose regulation remains unclear. Here, we activated mediobasal hypothalamus (MBH) JAZF1 in high‐fat diet (HFD)‐fed rats by an adenovirus expressing JAZF1 (Ad‐ JAZF1 ). We evaluated the changes in the hypothalamic insulin receptor (InsR)‐PI3K‐Akt‐AMPK pathway and hepatic glucose production (HGP). To investigate the impact of MBH Ad‐ JAZF1 on HGP, we activated MBH JAZF1 in the presence or absence of ATP‐dependent potassium (KATP ) channel inhibition, hepatic branch vagotomy (HVG), or an AMPK activator (AICAR). In HFD‐fed rats, MBH Ad‐ JAZF1 decreased body weight and food intake, and inhibited HGP by increasing hepatic insulin signaling. Under insulin stimulation, MBH Ad‐ JAZF1 increased InsR and Akt phosphorylation, and phosphatidylinositol 3, 4, 5‐trisphosphate (PIP3) formation; however, AMPK phosphorylation was decreased in the hypothalamus. The positive effect of MBH JAZF1 on hepatic insulin signaling and HGP was prevented by treatment with a KATP channel inhibitor or HVG. The metabolic impact of hypothalamic JAZF1 was also blocked by MBH AICAR. Ad‐ JAZF1 treatment in SH‐SY5Y cells resulted in an elevation of InsR and Akt phosphorylation following insulin stimulation. Our findings show that hypothalamic JAZF1 regulates HGP via the InsR‐PI3K‐Akt‐AMPK pathway and KATP channels.